Spectral fingerprints of earth-like planets around FGK stars - Rugheimer, S; Kaltenegger, L; Zsom, A; Segura, A; Sasselov, D (Mary Ann Liebert, 2013)
We present model atmospheres for an Earth-like planet orbiting the entire grid of main sequence FGK stars with effective temperatures ranging from Teff=4250 K to Teff=7000 K in 250 K intervals. We have modeled the remotely detectable spectra of Earth-like planets for clear and cloudy atmospheres at the 1 AU equivalent distance from the VIS to IR (0.4 to 20 μm) to compare detectability of features in different wavelength ranges in accordance with the James Webb Space Telescope and future design concepts to characterize exo-Earths. We have also explored the effect of the stellar UV levels as well as spectral energy distribution on a terrestrial atmosphere, concentrating on detectable atmospheric features that indicate habitability on Earth, namely, H2O, O3, CH4, N2O, and CH3Cl. The increase in UV dominates changes of O3, OH, CH4, N2O, and CH3Cl, whereas the increase in stellar temperature dominates changes in H2O. The overall effect as stellar effective temperatures and corresponding UV increase is a lower surface temperature of the planet due to a bigger part of the stellar flux being reflected at short wavelengths, as well as increased photolysis. Earth-like atmosphere models show more O3 and OH but less stratospheric CH4, N2O, CH3Cl, and tropospheric H2O (but more stratospheric H2O) with increasing effective temperature of main sequence stars. The corresponding detectable spectral features, on the other hand, show different detectability depending on the wavelength observed. We concentrate on directly imaged planets here as a framework to interpret future light curves, direct imaging, and secondary eclipse measurements of atmospheres of terrestrial planets in the habitable zone at varying orbital positions.